KESELAMATAN AGAMA SELAIN ISLAM: KAJIAN PLURALISME TERHADAP QS. AL-BAQARAH AYAT 62 DALAM TAFSIR IBNU KATSIR - Pandyadinnata, Arjuna; Thohir, Umar Faruq (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This problem is related to the phenomenon of religious salvation in the midst of religious diversity where this problem arises various views on how the salvation of religions other than Islam in the afterlife, especially in the context of religious pluralism, namely an understanding that says that all religions are equally true and all religions will receive salvation. This research is qualitative with a library research approach and focuses on the content analysis method, namely focusing on the interpretation of Ibn Kathir's book in the form of documentation in QS. Al-Baqarah verse 62. The results of the study show that Ibn Kathir's interpretation of QS. Al-Baqarah verse 62 referred to the Jews, Christians, and Sabi'in, namely a previous people who were sent before the coming of the Prophet Muhammad SAW as the last of the Prophets and Apostles. For those who believe in Allah, the hereafter, do good, and follow the teachings or sharia of their Prophet during his time, then they are the ones who will receive salvation. So Ibn Katsir's interpretation shows that he rejects pluralism and an exclusive attitude, salvation can be achieved by following the Shari'a of the Prophet Muhammad SAW as the last Prophet and Messenger, and must embrace Islam. So that religions other than Islam cannot gain salvation in the afterlife, except by embracing Islam and following the Shari'a of the Prophet Muhammad SAW. The relevance of Ibn Kathir's interpretation when connected to today's plural society remains relevant as long as we have to be tolerant, respect each other, and respect those with different beliefs from us, even if their teachings are different from ours and are wrong. We do not need to assume that all religions are the same and correct, such as pluralism.